Ligand Radicals as Modular Organic Electron Spin Qubits. Issue 66 (2nd November 2018) - McGuire, Jake; Miras, Haralampos N.; Donahue, James P.; Richards, Emma; Sproules, Stephen
Abstract: The intrinsic redox activity of the dithiolene ligand is presented here as the novel spin host in the design of a prototype molecular electron spin qubit, where the traditional roles of the metal and ligand components in coordination complexes are inverted. A series of paramagnetic bis(dithiolene) complexes with group 10 metals—nickel, palladium, platinum—provides a backdrop to investigate the spin dynamics of the organic ligand radical using pulsed EPR spectroscopy. The temperature dependence of the phase memory time ( T M ) is shown to be dependent on the identity of the diamagnetic metal ion, with the short times recorded for platinum a consequence of a diminishing spin‐lattice ( T 1 ) relaxation time driven by spin‐orbit coupling. The utility of the radical ligand spin center is confirmed when it delivers one of the longest phase memory times ever recorded for a molecular two‐qubit prototype. Abstract : Do your qubit : The redox‐active dithiolene ligand is presented as a novel spin host in the design of prototype molecular electron spin qubits. The modularity of the metallodithiolene motif is demonstrated in the assemblage of a prototype two‐qubit system with one of the longest reported phase memory times for a coordination complex (see Figure).